Practical project management for building and construction - Ottosson, Hans. (ESI International project management series ;, 2013)
"With thousands of years of accumulated knowledge you must wonder if we builders really have anything new to learn. In the mid-1900s space flights, technologically advanced weapons systems and the computer industry began to run large and complex projects. New tools and techniques to succeed in complex projects were developed, primarily by NASA, the U.S. military and the IT-industry. Clients began to require some form of knowledge for Project Managers, who would manage a complex project. Needs and requirements for certification of Project Managers began to emerge. Actually, it is equally obvious that a Project Manager shall have a basic knowledge of how to run a 3 million dollars project , as it is to require a driving license for someone driving a motorcycle. Project management is a profession that requires specific knowledge and skills Local certification has existed for some time, but has not been widely practiced"--